2013
DOI: 10.1017/s0950268813000162
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with seroprevalence of Neospora caninum in dogs from urban and rural areas of milk and coffee production in Minas Gerais state, Brazil

Abstract: This study was conducted to determine the seroprevalence of anti-Neospora caninum antibodies and to investigate the risk factors related to seroprevalence in dogs from urban and rural areas with distinct economic activities (milk and coffee production) in Minas Gerais state, Brazil. For this purpose, blood samples from 703 dogs were collected and questionnaires addressing epidemiological aspects were completed by dog-owners. The sera were analysed for anti-N. caninum antibodies by indirect fluorescent antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 23 publications
1
19
0
1
Order By: Relevance
“…Serological surveys have also reported moderate to high levels of exposure to parasites such as Neospora caninum and T. gondii in dogs and cats in Brazil [151,168-173]. For instance, in a recent study carried out in south-eastern Brazil, 386 cats were assayed by indirect immunofluorescence antibody tests (IFAT) for the presence of antibodies against T. gondii and 63 (16.3%) of them were positive [172].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Serological surveys have also reported moderate to high levels of exposure to parasites such as Neospora caninum and T. gondii in dogs and cats in Brazil [151,168-173]. For instance, in a recent study carried out in south-eastern Brazil, 386 cats were assayed by indirect immunofluorescence antibody tests (IFAT) for the presence of antibodies against T. gondii and 63 (16.3%) of them were positive [172].…”
Section: Reviewmentioning
confidence: 99%
“…In another study conducted in south-eastern Brazil, 703 dogs from urban and rural areas were tested for N. caninum and 11.4% of them were positive. The likelihood of being positive to N. caninum was associated with dogs aged >4 years, guard dogs, hunting dogs, and with dogs from dairy farms with a history of bovine abortion [173]. In particular, among rural dogs, an association with seroprevalence was recorded for milk farms, dogs not fed with commercial food, hunting, and guard dogs.…”
Section: Reviewmentioning
confidence: 99%
“…Some studies have found an increased prevalence of antibodies against N. caninum in dogs from rural areas, suggesting a greater exposure to horizontal transmission from contact with aborted fetuses and fetal membranes (BRUHN et al, 2013;NOGUEIRA et al, 2013). However, De Sousa et al (2012) obtained a seroprevalence of 4.2%, with half of the dogs' population from urban areas and half from rural areas with no significant difference observed between the groups.…”
Section: Discussionmentioning
confidence: 96%
“…The age of dogs was a statistically significant factor in nine reports; older dogs were more likely to be seropositive FERNANDES et al, 2004;AZEVEDO et al, 2005;ANDREOTTI et al, 2006;CUNHA et al, 2008;MINERVINO et al, 2012;NOGUEIRA et al, 2013;BALTHAZAR et al, 2013;RAIMUNDO et al, 2015). Gender and breed were not associated with presence of antibodies.…”
Section: Epidemiologymentioning
confidence: 95%